Alternative sources of red dyes with high stability and antimicrobial properties: Towards an ecological and sustainable approach for five plant species from Madagascar. (20th June 2021) - Andriamanantena, Mahery; Razafimbelo, Fanjaniaina Fawbush; Raonizafinimanana, Béatrice; Cardon, Dominique; Danthu, Pascal; Lebeau, Juliana; Petit, Thomas; Caro, Yanis
Abstract: Artificial dyes from petrochemicals are extensively used in the numerous sectors. They have adverse effects on human health and environment. Economical and bio-friendly approaches are needed to extract and produce dyes in an ecological manner to replace the hazardous and toxic artificial ones. In this regard, exploiting the potential of natural dyes sources from unconventional plant species presumes a sustainable management of natural resources, and the development of eco-friendly processing extraction technologies with high efficiency, low toxicity and low environmental impacts. In Madagascar, five plant species including Acridocarpus excelsus, Ceriops tagal, Rhizophora mucronata, Woodfordia fruticosa and Xylocarpus granatum are traditionally used as sources of natural red dyes by Malagasy craftspersons for textile dyeing at a very small scale. This original work is based on this assessment. It demonstrated that biopigments extracted via a low-toxicity and highly-efficient pressurized liquid extraction (PLE method from barks adventive roots collected from these five plant species of Madagascar could be used as red dyestuffs. These dye plant extracts have been demonstrated as having, in term of colors, great pH stabilities within a pH range of 3–9 and thermal stability up to 200 °C. By their chemical properties, antioxidant and antimicrobial properties that could meet industrial application requirement. We are proposing lines of research that would improve the industrial sustainability and economic viability of the production of pigments extracted from Malagasy plant raw materials. The potential of PLE technique paired with eco-friendly solvents as an alternative method for the extraction and recovery of natural dyes is also discussed here. The valorization of these plant species using green technologies could enable the development of local sectors in Madagascar with wide potential of applications. However, issues related to development ethics, preservation of biological heritage and sustainable resource management must be carefully considered. Highlights: Coloring properties of dyestuffs from typical plant species from Madagascar are highlighted. Plant barks are promising sustainable sources of red dyestuff materials. W. fruticosa roots and A. excelsus barks revealed interesting coloring and antioxidant properties. Pressurized liquid solvent extraction of pigment is more efficient than traditional decoction. Their properties generate new areas of industrial applications beyond their traditional use.